2017
DOI: 10.1037/fam0000323
|View full text |Cite
|
Sign up to set email alerts
|

Coparenting relationship trajectories: Marital violence linked to change and variability after separation.

Abstract: Associations between marital intimate partner violence (IPV) and postseparation coparenting relationship trajectories were examined among 135 mothers who participated in five interviews at 3-month intervals in the year following their divorce filing. Growth curve analysis was conducted to assess change and variability in coparenting dimensions (i.e., conflict, support, communication about childrearing, and harassment) in the overall sample and by type of IPV. In the overall sample, coparenting conflict, commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 44 publications
0
33
0
1
Order By: Relevance
“…If replicated in future studies, this may mean that parallel or moderately involved coparenting might be recommended when former spouses are unable to coparent cooperatively. For example, ongoing physical or psychological abuse, extensive interparental conflicts, or other concerns related to parental fitness are real barriers to coparenting (Hardesty et al, 2017; Russell et al, 2016). In these situations, alternative forms of coparenting (e.g., moderately engaged or parallel) may better meet the needs of parents and youth.…”
Section: Discussionmentioning
confidence: 99%
“…If replicated in future studies, this may mean that parallel or moderately involved coparenting might be recommended when former spouses are unable to coparent cooperatively. For example, ongoing physical or psychological abuse, extensive interparental conflicts, or other concerns related to parental fitness are real barriers to coparenting (Hardesty et al, 2017; Russell et al, 2016). In these situations, alternative forms of coparenting (e.g., moderately engaged or parallel) may better meet the needs of parents and youth.…”
Section: Discussionmentioning
confidence: 99%
“…Health outcomes varied as a function of IPV type (i.e., SCV, CCV) as well as the presence of postseparation relationship stressors such as coparenting conflict and harassment. Additional work from this study (e.g., Hardesty et al, ) demonstrated that IPV significantly influenced trajectories of coparenting relationships following divorce. Shortt et al () also examined changes in violence over time and found that men's perpetration of physical aggression decreased but that physical aggression earlier in life predicted physical aggression 7 and 12 years later.…”
Section: Individual and Relational Contextsmentioning
confidence: 51%
“…Mothers who experienced CCV (vs. SCV or no violence) in marriage were found to have the lowest quality coparenting relationships in the year following a divorce filing (Hardesty et al, ). They also experienced the most harassment and coparenting conflict (Hardesty et al, ), more depression, PTSD, and physical health symptoms (Hardesty et al, ), and more volatility and unpredictable patterns of harassment and conflict (Hardesty et al, ). Despite considerable intrusion by former partners for years after separation, studies demonstrate mothers' and children's regenerative capacity to recover from IPV (Broughton & Ford‐Gilboe, ; Yu, Petit, Lansford, Dodge, & Bates, ).…”
Section: Individual and Relational Contextsmentioning
confidence: 99%
“…Role-playing helps familiarize team members with the protocols so they come more naturally to them if/when the specific scenarios arise and help us identify any gaps or flaws in our approaches. For example, in our study on IPV, divorce, and coparenting (Hardesty et al, 2017), RAs role-played how to handle screening calls if a former partner (instead of the woman we intended to reach) answered the phone. Situations like this can easily catch RAs off guard if they are not prepared to share a generic description of the study (e.g., on “women’s health”) or leave a general message.…”
Section: Research Procedures—issues Of Safety and Ethicsmentioning
confidence: 99%